The Kalinga legend of sleeping beauty: Cultural symbols and their role in indigenous identity and social cohesion - Wangiwang, Maryjoyce D. (International Journal of Innovative Research and Scientific Studies, 2025)
Legends and oral traditions play a crucial role in preserving cultural heritage and transmitting values across generations. In the Philippines, the Kalinga legend of Sleeping Beauty, distinct from its European counterpart, embodies the community’s experiences of conflict, identity, and resilience. Previous research on indigenous oral literature has largely focused on documenting texts and narrative structures, with limited attention to how symbolic dimensions function as carriers of cultural values. This study addresses that gap by examining the cultural symbols embedded in the legend and their significance for identity formation, social cohesion, and cultural preservation. The research employed a qualitative, interpretive design using symbolic and textual analysis, supported by semi-structured interviews with Kalinga elders and cultural bearers. Key symbols examined include the tribal war reference, mengor (hero), tribe, Mount Patukan, sawali wall, glass of water, moma, ullalim chant, salidsid dance, allap textile, tadok dance, seven days ritual, and inandila (rice delicacy), all situated within the context of Kalinga cosmology and oral tradition. Findings reveal that these cultural symbols function as both markers of collective identity and mechanisms of social cohesion, reinforcing values of unity, courage, and reverence for ancestral ties. Storytelling emerged as a dynamic medium of cultural transmission, serving as a living archive that educates younger generations and sustains resilience in the face of modern influences. The analysis also demonstrates how environmental symbols, particularly Mount Patukan, embody the interconnection between land, memory, and cultural continuity, reflecting the community’s deep relationship with nature. This study concludes that the Kalinga Sleeping Beauty legend represents more than a tale of romantic tragedy; it is a symbolic narrative that safeguards indigenous identity, strengthens social solidarity, and offers insights for integrating oral traditions into contemporary education. By positioning indigenous narratives as pedagogical resources, the research advances scholarship on oral literature, cultural preservation, and sustainability education.